2011
DOI: 10.1021/jp204735d
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Aggregations of Monolayer-Protected Gold Nanoparticles in Solvents

Abstract: Coarse-grained (CG) molecular dynamics (MD) simulations were carried out to investigate the dynamics of 2.2 nm monolayer-protected gold nanoparticles (AuNPs) in solvents. The effects of ligand length, ligand terminal chemistry, solvents, and temperature were examined. It was found that AuNPs with unmodified alkanethiol ligands formed stable aggregates in water in the time scale of hundreds of nanoseconds (eight nanoparticles). In a particular case, the AuNPs aggregated into an infinite, one-dimensional chainli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 35 publications
2
67
1
Order By: Relevance
“…The CG parameters for CHOL and FFA were taken from our earlier work29. The CG parameters of thiol coated AuNPs were taken from previous simulation studies25262729. The simulations were carried out in NVT and NPT ensemble using the GROMACS MD package363738.…”
Section: System Models and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CG parameters for CHOL and FFA were taken from our earlier work29. The CG parameters of thiol coated AuNPs were taken from previous simulation studies25262729. The simulations were carried out in NVT and NPT ensemble using the GROMACS MD package363738.…”
Section: System Models and Methodsmentioning
confidence: 99%
“…synthesized thiol coated colloidal AuNP of 3.75 ± 0.06 nm and based on their experiments, a new Coarse Grained (CG) model of AuNP was developed. JQ Lin et al 252627. developed a CG model for AuNPs and verified against experimental data.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…J Lin et al [29][30][31] performed series of MD simulations to study the interaction of lipid bilayers with the alkyl thiol coated AuNP. They developed a coarse-grained model for gold nanoparticles and verified against experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies found crystalline NP structures with elastic moduli on the order of 1 GPa. At the liquid/vapor interface the aggregation of encoded NPs were studied by Lane and Grest [13] and Lin et al [14].…”
mentioning
confidence: 99%